Émigré creativity in a historical context - Altabaa, Homam; Hamawiya, Adham (Society, 2019)
Émigré writers such as Kahlil Gibran and Mikhail Naimy proved that it is possible to transcend their historical limitations to become leading literary figures. An examination of the historical context of these writers is important for a rich understanding of their works. The themes addressed in such literary works are better appreciated within their cultural environment, and not as objects detached from their times, author and readers1. It can be rightfully argued that such works cannot be fully appreciated without delving into the intricacies of the political ideologies and economic crises of previous centuries. This article does not aim to perform such an undertaking, regardless of its literary merit; however, it presents an overview of the historical context surrounding the Émigré literary movement as a product of two cultures bridged by immigration at the turn of the 20th century. This is based on the belief that a profound critical engagement with Émigré works is better achieved with an examination of their historical and literary background. Thus, this article serves as a foundation for profound literary analyses of Émigré works.